Stakeholder interactions and capacity development for innovation and adoption of agricultural technologies: the case of banana value chain in Uganda - Babu, Chandra Suresh (University of Pretoria, 2024)
Thesis (PhD (Agrarian Extension))--University of Pretoria, 2024.